Recent Results from the T2K Experiment - Abe, K; Abgrall, N; Aihara, H; Akiri, T; Andreopoulos, C; Aoki, S; Ariga, A; Ariga, T; Assylbekov, S; Autiero, D; Barbi, M; Barker, G; et al. (2014)
The Tokai to Kamioka (T2K) experiment studies neutrino oscillations using a beam of muon neutrinos produced by an accelerator. The neutrinos travel from J-PARC on the east coast of Japan and are detected 295 kilometers further away in the Super-Kamiokande detector. A complex of near detectors located 280 meters away from the neutrino production target is used to better characterize the neutrino beam and reduce systematic uncertainties. The experiment aims at measuring electronic neutrino appearance (νμ→νe oscillation) to measure the neutrino mixing angle θ13, and muon neutrino disappearance to measure the neutrino mixing angle θ23 and mass splitting |δm322|. We report here electron neutrino appearance results using three years of data, recorded until the 2012 summer, as well as muon neutrino disappearance results based on the data coming from the first two years of the experiment. © 2013 Elsevier B.V.